The role of tourism and the importance of the stakeholder approach in creating team building programs - Vujičić, Milica (Turizam, 2019)
Team building is a process that aims at improving the performance of a group of people working together to achieve a common goal. Team buildings are an indispensable part of corporate activities of main tourism stakeholders including hospitality service providers, event organizers, transport companies, and many others. To assess the current state of tailor-made team building in Serbia an in-depth interview encompassed hotel managers, consultant agencies directors, head of the travel agencies, event organizer and other. The sample size was 10 respondents. All of the respondents are in some way connected and in line with team building work or decision making. The research was conducted during August and September of 2015. The study found some interesting results that most of the market share of the corporate events are under the hotels, followed by consultant agencies and only 1% is within travel agencies. Seasonality is also noticed, spring and autumn are most frequent with team buildings. Group mostly consists out of 30 to 60 participants and the duration is 2 to 3 days. Beside entreating part of the event, most of the activities are aimed at employee development. Research also found some barriers from the lack of budget, to the heterogenic group, to many details in the team building request and other. Further research could give some interesting recommendations and suggestions on how to improve and exploit this tourism and event market.